2020
DOI: 10.32890/jbma2013.3.0.8882
|View full text |Cite
|
Sign up to set email alerts
|

Owner Specific Factors, Firm Specific Factors, Internationalisation and Performance of SMEs in Sri Lanka: A Conceptual Framework

Abstract: As SMEs are internationalising at a faster rate today, theories that can explain SME internationalisation and performance are of extreme importance. At present there is no agreement among scholars on a single theoretical framework on SME internationalisation and performance. The literature suggested that contemporary firm performance is not associated with traditional factors. However, firm internationalisation and SME performance seem to be directly associated with unobservable owner and firm factors. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Several studies have argued the positive impact of branding and firms' export performance (Efrat and Asseraf, 2019;Imran et al, 2018;Wong and Merrilees, 2007;Spyropoulou et al, 2011;Pyper et al, 2015). However, Mudalige et al (2020) have found the relationship between EO, brand orientation and international performance of SMEs in Sri Lanka. Similarly, Mansour (2021) has argued that branding and commitment positively affect the international marketing strategy and SMEs' international performance.…”
Section: Entrepreneurial Orientation Brand Differentiation and Export...mentioning
confidence: 96%
“…Several studies have argued the positive impact of branding and firms' export performance (Efrat and Asseraf, 2019;Imran et al, 2018;Wong and Merrilees, 2007;Spyropoulou et al, 2011;Pyper et al, 2015). However, Mudalige et al (2020) have found the relationship between EO, brand orientation and international performance of SMEs in Sri Lanka. Similarly, Mansour (2021) has argued that branding and commitment positively affect the international marketing strategy and SMEs' international performance.…”
Section: Entrepreneurial Orientation Brand Differentiation and Export...mentioning
confidence: 96%
“…DCs have been considered a fundamental view for understanding how companies in the tourism sector, and hotels in particular, can respond to environmental changes and improve their performance in turbulent situations (Marco-Lajara et al, 2021). Through this perspective, some studies have tried to determine whether more internationalized companies achieve better results (Mudalige, 2015;Pehrsson et al, 2015). But in an environment as changing as the current one and within the framework of sustainability requirements, it is necessary to know the factors that can help firms be more competitive, achieve sustainability and be more responsible, considering the win-win relationship between companies and society to be important.…”
Section: Introductionmentioning
confidence: 99%